Does more intense competition lead to higher growth? - Dutz, Mark Andrew 1951-; Hayri, Aydın 1965- (CEPR, 1999)
The relationship between the overall intensity of competition in an economy and its long-run growth is an open question in economics. Theoretically, there is no clear-cut answer. However, there exists empirical evidence that in some sectors more competition leads to more innovation and accelerates productivity growth. To complement these findings and capture economy-wide effects, we conduct a cross-country study. We examine the impact of intensity of domestic competition beyond trade liberalisation on growth. Our findings indicate that the effectiveness of antitrust and competition policy enforcement is positively associated with long-run growth
Auch als el. Ress. verfügbar
Keywords: Konkurrence; Økonomisk vækst